Yahoo奇摩 網頁搜尋

  1. identity 相關
    廣告
  1. ...you want to ask the gernal meaning of Identities in Eng. I have cheak it for...killer. 留在槍上的指紋證實他就是殺人者。 Identity of interests is the bond that...

  2. A) (x-2)^2=x^2-2x+4 B) (2-a-b)^2=[2-(a+b)]^2 =4-4(a+b)+(a+b)^2 =4-4a-4b+a^2+2ab+b^2

  3. (a) Expand (2k+u)2 (2k+u)2 = (2k)2 + 4ku + u2 = 4k2 + 4ku + u2 (b) Using the result of (a), expand (2k+x-y)2 (2k+x-y)2 = [(2k+x) - y]2 = (2k+x)2 - 2(2k+x)y + y2 Using the result of (a) : (2k+u)2 = 4k2 + 4ku +u2 (2k+x-y)2 = (4k2 + 4kx + x2) - 2(2k+x)y + y2 = 4k2 + 4kx + x2 - 4ky - 2xy + y2 = 4k2 + x2 + y2 + 4kx - 4ky - 2xy

  4. 6(a+1)²+4(a+1) = 2(a+1) [3(a+1)+2] = 2(a+1) (3a+3+2) = 2(a+1) (3a+5)

  5. (x+y)^2 =x^2+y^2+2xy =100+2(48) =196 (x-y)^2 =x^2+y^2-2xy =100-2(48) =4 2010-12-30 12:54:30 補充: part b is exactly the same. c(i) (x+y)^2 (x-y)^2 =[(x+y)(x-y)]^2 =(x^2-y^2)^2 =x^4 - 2x^2 y^2 + y^4 (ii) x^4- 2x^2 y^2 +y^4 -84 =(x+y)^2 (x-y)^2-84 (using part c i) =(196)(4)-84 (using part b) =700

  6. What do you want to do with Q. 1-4? Expansion? 1. -2(3x+4) A. -2(3x+4) = -6x-8 2. (6-3x)(-8) A. (6-3x)(-8) = -48+24x 3. 3x(4x-5) A. 3x(4x-5) = 12x^2-15x 4. (-5x+8)(-7x) A. (-5x+8)(-7x) = 35^2-56x 5. (x+1)^2 A. (x+1)^2 = x^2+2x+1 6. (x-2)^2 A...

  7. 1)(x+7)(2x-5)=Ax^2+Bx+C LHS = 2x^2 + 14x - 5x - 35 = 2x^2 + 9x - 35 So A = 2 , B = 9 , C = - 35 2)A(5-x)=2(Bx+45) -Ax + 5A = 2Bx + 90 So -A = 2B...(1) 5A = 90...(2) By (2...

  8. 36a^2-25(3b-c)^2 =(6a)^2-[5(3b-c)]^2 =[6a+5(3b-c)][6a-5(3b-c)] =(6a+15b-5c)(6a-15b+5c)// 100(2d-e)^2-49f^2 =[10(2d-e)]^2-(7f)^2 =[10(2d-e)+7f][10(2d-e)-7f] =(20d-10e+7f)(20d-10e-7f)// 95g-6h0^2-16(4g-3h)^2 =(5g-6h)^2-16(4g-3h)^2----? =[(5g-6h)^2-[4(4g-3h)]^2 =[(5g-6h)+4(4g-3h)][[(5g-6h)-4(4g-3h)] =(5g-6h+16g-12h)(5g-6h-16g+12h) =(21g-18h)(-11g+6h) =3(7g-6h)(6h...

  9. 2Ax=-3x A=-3/2 -B=9 B=-9

  10. As follows~ 圖片參考:http://i248.photobucket.com/albums/gg191/ncy_0916/maths32.jpg?t=1218076303 2008-08-07 10:33:02 補充: By using the idenities: a^2 - b^2 = (a - b)(a + b) (a - b)^2 = a^2 - 2ab + b^2 2008-08-07 10:34:03 補充: 2)(1 - x)(1 + x) = 1 - x^2 (1 - x^2)(1 + x^2) = 1 - (x...

  1. identity 相關
    廣告